The central role of thrombin in bleeding disorders. (November 2019) - Negrier, Claude; Shima, Midori; Hoffman, Maureane
Abstract: Maintaining normal hemostasis relies on a regulated system of procoagulant and anticoagulant pathways, and disruption of these processes leads to the loss of hemostatic control, with the potential for excessive bleeding or thrombosis. Evaluation of bleeding disorders has conventionally been achieved by laboratory assays that measure the activity of individual coagulation factors. While such assays have proven effective for detecting abnormalities of the coagulation system and aiding diagnosis, inherent limitations prevent them from capturing a complete picture of hemostatic function. An improved understanding of thrombin activity and its central role in hemostasis and bleeding disorders has led to the clinical development of global assays that are more physiologically relevant than traditional assays; furthermore, these global assays are able to monitor responses to therapy. In this review, we provide an overview of the role of thrombin in hemostasis, and describe the clinical benefits of thrombin monitoring in patients with bleeding disorders. Moreover, we discuss recent advances in thrombin-targeting therapeutic strategies that aim to correct thrombin deficiency and prevent bleeding in patients with hemophilia and other rare bleeding disorders.